DIGITAL TRANSFORMATION IN HIGHER EDUCATION: STUDENT ENGAGEMENT AND THE EFFECTIVENESS OF DIGITAL LEARNING RESOURCES (Global Conference on Medical and Health Sciences, 2026)
The rapid development of digital technologies has significantly transformed higher education systems worldwide. Universities increasingly integrate digital learning resources, online platforms, and virtual learning environments into their teaching practices. This transformation has accelerated particularly in recent years due to the expansion of online education and the growing demand for flexible learning opportunities. The purpose of this study is to analyze the role of digital learning resources in improving student engagement and learning outcomes in higher education. The research is based on a review of contemporary academic literature and international reports produced by leading educational organizations. Special attention is given to the impact of digital platforms, multimedia learning tools, and interactive educational technologies on students’ motivation and participation. The article also discusses the challenges associated with digital education, including technological inequalities, digital literacy gaps, and pedagogical adaptation. The study concludes that digital learning resources, when used strategically and pedagogically, can significantly enhance student engagement and contribute to more effective educational processes in universities.
Keywords: digital education, higher education, student engagement, digital learning resources, online learning